Effects of Nitrogen Application on Nitrogen Fixation in Common Bean Production - Reinprecht, Yarmilla; Schram, Lyndsay; Marsolais, Frédéric; Smith, Thomas H.; Hill, Brett; Pauls, Karl Peter (Frontiers in Plant Science, 2020)
The nitrogen fixing ability of common bean (Phaseolus vulgaris L.) in association with rhizobia is often characterized as poor, compared to other legumes, and nitrogen fertilizers are commonly used in bean production to achieve high yields. However, the addition of nitrogen inhibits nitrogen fixation and plants cannot utilize all the nitrogen fertilizer that is applied to the soil leading to runoff and groundwater contamination. The overall objective of this work is to reduce nitrogen fertilizer use in common bean production. This would be a major advance in profitability for the common bean industry in Canada and would significantly improve the ecological footprint of the crop. In the current work, 22 bean genotypes [including a non-nodulating mutant (R99)] were screened in plots at the Elora research station (University of Guelph) for their capacity to fix atmospheric nitrogen in the presence (R) or absence (NoR) of rhizobia and with 100 kg ha-1 nitrogen (N) or without nitrogen fertilization [no nitrogen (NoN)]. Both, nitrogen and rhizobia were added at planting. The genotypes were evaluated in replicated split-split-plot designs on nitrogen poor soils over three years (2016, 2017 and 2018) for: nitrogen derived from atmosphere (%Ndfa) in the seed, yield and a number of yield-related traits. Significant differences among genotypes were identified for all analyzed traits in all three years and the level of nitrogen significantly affected most of the traits, including %Ndfa and yield. In contrast, application of rhizobia significantly affected only few traits and the effect was inconsistent among the years. A Ndfa-derived index (%NdfaRN/%NdfaR) indicated that nitrogen application reduced symbiotic nitrogen fixation (SNF) to different degrees in different bean genotypes. This variation suggests that SNF in common bean can be improved through breeding and selection for the ability of bean genotypes to fix nitrogen in the presence of reduced fertilizer levels.